Improved jellyfish gelatin quality through ultrasound-assisted salt removal and an extraction process - Artima Lueyot; Benjamaporn Wonganu; Vilai Rungsardthong; Savitri Vatanyoopaisarn; Pokkwan Hutangura; Pisit Wongsa-Ngasri; Sittiruk Roytrakul; Sawanya Charoenlappanit; Tao Wu; Benjawan Thumthanaruk (PLoS ONE, 2022)
The use of by-products of salted jellyfish for gelatin production offers valuable gelatin products rather than animal feed. Several washes or washing machines have reported removing salt in salted jellyfish. However, the green ultrasound technique has never been reported for the desalination of salted jellyfish. The objectives were to determine how effectively the raw material’s salt removal was done by combining the traditional wash and then subjected to the ultrasonic waves in a sonication bath for 20–100 min. For gelatin production, the ultrasonicated jellyfish by-products were pretreated with sodium hydroxide and hydrochloric acid, washed, and extracted with hot water for 4, 6, and 8 h. Results showed that the increased duration of ultrasound time increased the desalination rate. The highest desalination rate of 100% was achieved using 100 min ultrasonic time operated at a fixed frequency (40 kHz) and power (220 W). The jellyfish gelatin extracted for 4, 6, and 8 h showed gel strengths in 121–447, 120–278, and 91–248 g. The 80 min ultrasonicated sample and hot water extraction for 8 h (JFG80-8) showed the highest gel yield of 32.69%, with a gel strength of 114.92 g. Still, the 40 min ultrasonicated sample with 4 h of extraction delivered the highest gel strength of 447.01 g (JFG40-4) and the lower yield of 10.60%. The melting and gelling temperatures of jellyfish gelatin from ultrasonicated samples ranged from 15–25°C and 5–12°C, which are lower than bovine gelatin (BG) and fish gelatin (FG). Monitored by FITR, the synergistic effect of extended sonication time (from 20–100 min) with 4 h extraction time at 80 °C caused amide I, II, and III changes. Based on the proteomic results, the peptide similarity of JFG40-4, having the highest gel strength, was 17, 23, or 20 peptides compared to either BG, FG, or JFG100-8 having the lowest gel strength. The 14 peptides were similarly found in all JFG40-4, BG, and FG samples. In conclusion, for the first time in this report, the improved jellyfish gel can be achieved when combined with traditional wash and 40 min ultrasonication of desalted jellyfish and extraction time of 4 h at 80 °C.